2013
DOI: 10.1002/anie.201304359
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Oxidation of Unactivated CH Bonds with Hypervalent Iodine(III) Reagents

Abstract: Scheme 2. Proposed pathway for the formation of iodanyl radical. Scheme 3. Oxidation of methyl valerate with 2 and 3 d.Scheme 4. Hypervalent iodine(III) reagents 3. [12] naph = naphthalene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 37 publications
6
50
0
1
Order By: Relevance
“…As comparison, the C–H chlorination of norbornane with common reagents (e.g., Cl 2 or SO 2 Cl 2 ) leads to mixtures of the exo and endo isomers. 11 Both trans - and cis -1,2-dimethyl cyclohexanes– benchmark substrates for sterically-selective aliphatic C– H functionalizations 13 –exhibited excellent methylene selectivity (entries 10 and 11). Adamantane C–H chlorination involving chlorine free radical is documented to be a poorly selective process, with k t / k s = 3.5.…”
Section: Development Of the Aliphatic C–h Chlorinationmentioning
confidence: 99%
“…As comparison, the C–H chlorination of norbornane with common reagents (e.g., Cl 2 or SO 2 Cl 2 ) leads to mixtures of the exo and endo isomers. 11 Both trans - and cis -1,2-dimethyl cyclohexanes– benchmark substrates for sterically-selective aliphatic C– H functionalizations 13 –exhibited excellent methylene selectivity (entries 10 and 11). Adamantane C–H chlorination involving chlorine free radical is documented to be a poorly selective process, with k t / k s = 3.5.…”
Section: Development Of the Aliphatic C–h Chlorinationmentioning
confidence: 99%
“…[3] To date,an allylcobalt system is ar are example of ah omogenous arene hydrogenation catalyst with excellent cis selectivity (> 95 %), however it undergoes rapid deactivation with < 15 %c onversions achieved. [5][6][7][8] Single-site,m olecule-derived supported catalysts have attracted interest due to their hybrid character combining the complementary features of traditional hetero-and homogeneous systems. Owing to the versatility of alcohols and ketones as synthetic intermediates,t hese products can then be modified in many ways to afford avariety of valuable substances.…”
mentioning
confidence: 99%
“…[2,6] To address this challenge, superacid solvents, such as H 2 SO 4 , have been used to facilitate anion ligand dissociation and alkane coordination. [2] We have recently reported that main-group electrophilic salts with filled d orbitals (d 10 ) such as Tl III (TFA) 3 and Pb IV (TFA) 4 (TFA = trifluoroacetate) promote efficient and selective stoichiometric CH activation and functionalization of methane (MeH), ethane (EtH), and propane (PrH) in more practical weaker acid solvents (HOAc, HTFA). [2] We have recently reported that main-group electrophilic salts with filled d orbitals (d 10 ) such as Tl III (TFA) 3 and Pb IV (TFA) 4 (TFA = trifluoroacetate) promote efficient and selective stoichiometric CH activation and functionalization of methane (MeH), ethane (EtH), and propane (PrH) in more practical weaker acid solvents (HOAc, HTFA).…”
mentioning
confidence: 99%